UMROH PILGRIMAGE SATISFACTION REVIEWED FROM SERVICE, FACILITIES, PRICE PERCEPTION, AND TRUST - Rachmi, Novita; Istiatin, Istiatin; Sudarwati, Sudarwati (STIE Pelita Nusantara Semarang, 2025)
Abstract:This study aims to determine the satisfaction of Umrah pilgrims in terms of service, facilities, price perception, and trust at the Surya Madina Surakarta Umrah Bureau. The research method used in this study is quantitative descriptive research. The sampling technique used is simple random sampling, randomly selected 79 pilgrims, from a population of 786 Umrah pilgrims at the Surya Madina Umrah Bureau. The data collection technique uses a questionnaire that is tested for validity and reliability, while the data analysis technique uses multiple linear regression methods. Data processing in this study uses SPSS software version 30. The results of this study indicate that service, price perception, and trust have a positive and significant effect partially on the satisfaction of Umrah pilgrims at the Surya Madina Umrah Bureau. While facilities have a positive but not significant effect on the satisfaction of Umrah pilgrims at the Surya Madina Umrah Bureau.